Fabrication And Characterization Of Poly(3-Hydroxybutyrate-Co-4- Hydroxybutyrate)/Chitosan Blend And Its Silver Nanocomposite Material - Mathava, Rennukka (2014)
A desirable wound dressing should be able to accelerate wound healing with infection controlled effect. Other than that, there are few important features of the wound dressing such as ability to absorb the exudates from wound and to be biodegradable. Therefore, a new blend material was fabricated from poly(3- hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] and chitosan through simple solvent casting method as they meet the essential requirements of the wound dressing. The impact of different contents of chitosan (5, 10, 15 and 20 wt%) and compositions of 4HB monomer (10, 18, 28 and 44%) towards the properties of hybrid film was determined. The interaction between P(3HB-co-4HB) and chitosan in the form of intermolecular hydrogen bonding was confirmed with the shift in the carbonyl group of copolymer and amide group of chitosan in the FTIR spectra. Film solubility was decreased from 10% to 5% whereas water absorption capacity was increased up to 59-68% when the content of chitosan was 20 wt% in each of the copolymer. Besides, blending with 20 wt% of chitosan improved the elongation at break and lowered the Young’s modulus of the copolymers. In term of thermal properties, depression in the melting temperature and increment of thermal stability were observed. The microscopic images indicated that the blend films had porous and rough surface. Furthermore, they exhibited good inhibition against Escherichia coli (22%) and Staphylococcus aureus (11%). P(3HB-co-4HB)/20 wt% chitosan were more hydrophilic, flexible, porous, rougher and bactericidal.